Promoting Extreme Violence: Visual and Narrative Analysis of Select Ultraviolent Terror Propaganda Videos Produced by the Islamic State of Iraq and Syria (ISIS) in 2015 and 2016. Issue 8 (16th November 2020) - Venkatesh, Vivek; Podoshen, Jeffrey S.; Wallin, Jason; Rabah, Jihan; Glass, Daniel
ABSTRACT: This paper examines aspects of violent, traumatic terrorist video propaganda produced by the Islamic State of Iraq and Syria (ISIS) within the theoretical confines of abjection and the use of utopian/dystopian themes. These themes have been present in a number of studies that have examined consumption of the dark dystopic variety. We seek to elucidate on the use of specific techniques and narratives that are relatively new to the global propaganda consumerspace and that relate to horrific violence. Our work here is centered on interpretative analysis and theory building that we believe can assist in understanding and interpreting post-apocalyptic and abject-oriented campaigns in the age of social media and rapid transmission of multimedia communications. In the present analysis, we examine eight ISIS videos created and released in 2015 and 2016. All of the videos chosen for analysis have utilized techniques related to abjection, shock, and horror, often culminating in the filming of the murder of ISIS's enemies or place-based destruction of holy sites in the Middle East. We use inductive content analytic techniques in the contexts of consumer culture, "cinemas of attraction, " and pornography of violence to propose an extension of existing frameworks of terrorism and propaganda theory.